Design of a Wind Pipe Installation Using a Solenoid Valve at the Piksi Ganesha Indonesia Polytechnic Laboratory - Bahtiar Wilantara; Hamid Nasrullah; Wahyu Alif Ramadhan; Lukman Novaludin (Politeknik Piksi Ganesha Indonesia, 2022)
This study aims to design a wind pipe installation using a solenoid valve in Piksi Ganesha Indonesia Polytechnic laboratory. The research used the R & D (Research and Development) method. The research results are: 1) the testing of the use of a wind pipe installation using a solenoid valve produced an average wind pressure of 88.57 psi.; (2) the product usability test was 70% which belongs to the “very useful” category for use in the laboratory of the Indonesian Polytechnic Piksi Ganesha; (3) at a pressure of 20 psi when the solenoid valve was open, the air pressure released by the air duster gun increased gradually according to the compressor capacity, while at a pressure of 20 psi when the solenoid valve was closed, the air duster gun could not release the air because the solenoid valve was closed, so the wind could not move towards the air duster gun.